Nonlocality activation in a photonic quantum network - Villegas-Aguilar, Luis; Polino, Emanuele; Ghafari, Farzad; Quintino, Marco Túlio; Laverick, Kiarn T.; Berkman, Ian R.; Rogge, Sven; Shalm, Lynden K.; Tischler, Nora; Cavalcanti, Eric G.; Slussarenko, Sergei; Pryde, Geoff J. (Nature communications, 2024)
Bell nonlocality refers to correlations between two distant, entangled particles that challenge classical notions of local causality. Beyond its foundational significance, nonlocality is crucial for device-independent technologies like quantum key distribution and randomness generation. Nonlocality quickly deteriorates in the presence of noise, and restoring nonlocal correlations requires additional resources. These often come in the form of many instances of the input state and joint measurements, incurring a significant resource overhead. Here, we experimentally demonstrate that single copies of Bell-local states, incapable of violating any standard Bell inequality, can give rise to nonlocality after being embedded into a quantum network of multiple parties. We subject the initial entangled state to a quantum channel that broadcasts part of the state to two independent receivers and certify the nonlocality in the resulting network by violating a tailored Bell-like inequality. We obtain these results without making any assumptions about the prepared states, the quantum channel, or the validity of quantum theory. Our findings have fundamental implications for nonlocality and enable the practical use of nonlocal correlations in real-world applications, even in scenarios dominated by noise. Entangled local states can be made capable of violating Bell inequalities via nonlocality activation. Typical theoretical approaches require processing many copies of the original state and performing joint measurements on the ensemble. Here, instead, the authors experimentally demonstrate how to do so using a single copy of the state, broadcasting it to two spatially separated parties within a three-node network.